Behaviour’s Farmer to the Risk of Broccoli Farming in Kutabawa Village, Sub-District Karangreja, Purbalingga District - Pujiharto, Sri Wahyuni (International Journal of Advanced Science and Technology, 2020)
This research aims to (1) measure the production and income risk of broccoli farm; (2) analyze the behaviour of farmers against risk (risk lover, risk-neutral, or risk averter); (3) analyze the factors that influence the behaviour of farmers against the risk of broccoli farming. The study was conducted in the Kutabawa Village Area, Karangreja Sub-district, Purbalingga Regency. The analysis used in this study was by calculating the variance and the smallest real difference test (Ordinary Least Square). The number of samples was 52 broccoli farmers. The results showed that (1) the risk of broccoli production in the rainy season (0.170 or 17.0%), the dry season (0.168 or 16.8%). Meanwhile, the risk of broccoli income in the dry season (0.877 or 87.7%), rainy season (0.808 or 80.8%); 2) broccoli farmers in the research sites are mostly risk-averter; (3) factors that affect the increase of farmers’ reluctance towards the risk is the level of pest attack and the risk of production. Meanwhile, the planting area, farmers’ education, and non-farm incomes affected to decrease the farmers’ reluctance or increase the farmer’s courage to face the risk. Keywords: risks taking, Broccoli cultivation, Purbalingga.